Kewarisan Beda Agama (Studi Pandangan Muaz bin Jabal) - Riyanta Riyanta (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
Genealogy relationship to every aspect of life is a link for a generation to the next one. The continuity of generation needs the preparation and supply, materially or immaterially, in order to be able to exist and survive. Al-Quran even suggested Moslem not to leave the weak generation. Therefore, genealogy relationship was believed as a main cause of inheritance transition from the dead to the heir. The problem appears when the Moslem has to bequeath to non Moslem. Al-Quran does not explain it, even the tradition forbade the interreligious inheritance, whereas the social context demands to treat the other way. The dialectic between law and social demand became a big problem to the Islamic law of inheritance. The problem of interreligious inheritance appeared when the relationship between Moslem and non Moslem was re-discussed by some social groups. Moreover, it became attention of Moslem thinkers since its formation, such as Mua? bin Jabal. His decision to share the inheritance from Moslem to non Moslem is an innovation that is needed to appreciate. He braves to find another way by ignoring the textual law towards the contextual law without leaving the essence of shariah. Besides it is for human benefit, it is also for implementing uptodate Islamic law.